2015
DOI: 10.18388/abp.2015_1045
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of antigen presenting and secretory functions of monocytic cells by Helicobacter pylori antigens in relation to impairment of lymphocyte expansion

Abstract: The role of Helicobacter pylori (H. pylori) antigens in driving a specific immune response against the bacteria causing gastroduodenal disorders is poorly understood. Using a guinea pig model mimicking the natural history of H. pylori infection, we evaluated the effectiveness of immature and mature macrophages in promoting the blastogenesis of splenocytes from H. pylori infected and uninfected animals, in response to H. pylori antigens: glycine acid extract (GE), cytotoxin associated gene A protein (CagA), ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…H. pylori antigens penetrating across the gastric epithelium, can be processed in lamina propria by macrophages via PRR and presented to T lymphocytes[8,19,20]. However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94]. It also downregulates the phagocytic potential of macrophages[44] and decreases the cytotoxic activity of NK cells[45,68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H. pylori antigens penetrating across the gastric epithelium, can be processed in lamina propria by macrophages via PRR and presented to T lymphocytes[8,19,20]. However, it has been shown that H. pylori LPS is able to downregulate the lymphocyte blastogenic response, probably due to the interference with the process of macrophage maturation[46-48,94]. It also downregulates the phagocytic potential of macrophages[44] and decreases the cytotoxic activity of NK cells[45,68].…”
Section: Discussionmentioning
confidence: 99%
“…The antigen concentrations were adjusted experimentally or adopted from previously performed experiments[44,47,48,68]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to glycosylate host cholesterol is crucial for the virulence and antibiotic resistance of H. pylori [12]. H. pylori lipopolysaccharide (LPS), due to its structural features, induces a poor immune response and helps the bacteria develop into a chronic infection[13-18]. H. pylori LPS may carry various human Lewis (Le)-like antigens, which may play a role in autoimmunity.…”
Section: Microbiological Aspects Of H Pylorimentioning
confidence: 99%
“…The primary host immune response mechanisms, such as phagocytosis and natural killer (NK) cell activity, have been found to be downregulated by H. pylori LPS[17,18,39,40]. Adaptive immunity is also targeted by H. pylori compounds[1,15,41,42].…”
Section: Microbiological Aspects Of H Pylorimentioning
confidence: 99%